DAMPAK SELF EFFICACY DAN PEMAHAMAN MANAJEMEN KEUANGAN TERHADAP MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI S1 MANAJEMEN - Susanti, Ari; Rikah, Rikah (JAB (Jurnal Akuntansi & Bisnis), 2018)
Self-efficacy is the confidence of students to foster self-confidence, or 'self-confidence', in their own abilities. Understanding of Financial Management students, in this study wanted to find out, whether the S1 Management Study Program students were able to understand and follow financial management courses in accordance with the learning achievements to be achieved. This study aims at the effect of self efficacy, understanding of financial management on learning motivation in students. This research was conducted with a population of 100 respondents. Respondents in this study were students in semester 3 of Academic Year 2018/2019 at the Surakarta College of Economics and who were taking the Financial management course. The results of this study indicate that partially and together with the Self Efficacy variant (X1) affect the Student Learning Motivation (Y); Understanding of Financial Management (X2) has an effect on Student Learning Motivation (Y).Â Keywords: Understanding of Financial Management and Self Efficacy, Student Learning Motivation